Caracterização das práticas de cuidado em Saúde Mental de uma Comunidade Caiçara - Mendonça, Luiz Henrique Franco (Universidade Federal de São Carlos, 2023)
Ilha do Cardoso State Park is located in the extreme south of the state of São Paulo, in the municipality of Cananéia. It has about 140 housing units, divided into specific communities of the traditional caiçara people, including Enseada da Baleia and Marujá. Geological and geopolitical changes, in addition to the recent pandemic of the new coronavirus, have altered communities' way of life, impacting their health and development. After a preliminary study using the current Psychosocial Care Network in the municipality, this research aimed to analyze the mental health care practices that the communities have, using the method of active participant observation of Rodas de Conversa in the communities of Enseada and Marujá. The qualitative analysis of the public data revealed the absence of public instituiions, either in the lack of specialized services, the difficulty in maintaining the river teams, or the lack of support to overcome limited situations. In the community of Enseada, the organization of the society and the continuous approach in its reconstruction after the compulsory change of location - which we interpret as a process of elaboration of a psychosocial trauma - generated the construction of more collective practices, such as the Dry Fish Workshop (which works along the lines of the Solidarity Economy) and the handicrafts, and which were appreciated as protective practices for the mental health of the people there. Such community care practices were not observed in the Community of Marujá, where many families do not have an associative bond and depend exclusively on informal work and social assistance benefits, leaving people more vulnerable concerning mental health problems. In both communities, care is predominantly exercised by women, generating an overload of activities, which reflects the gender inequalities observed by other researchers in Brazil and worldwide.
Caracterization of Mental Health Care Practices in a Caiçara Community
Keywords: Políticas públicas; Povos Tradicionais; Caiçaras; Saúde Mental; Práticas de Cuidado; Public Policies; Traditional People; Mental Health; Care Practices; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PROCESSOS GRUPAIS E DE COMUNICACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA